2020
DOI: 10.1126/sciadv.aay7148
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe sepsis with nanoparticulate cell-free DNA scavengers

Abstract: Severe sepsis represents a common, expensive, and deadly health care issue with limited therapeutic options. Gaining insights into the inflammatory dysregulation that causes sepsis would help develop new therapeutic strategies against severe sepsis. In this study, we identified the crucial role of cell-free DNA (cfDNA) in the regulation of the Toll-like receptor 9–mediated proinflammatory pathway in severe sepsis progression. Hypothesizing that removing cfDNA would be beneficial for sepsis treatment, we used p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 57 publications
5
88
1
1
Order By: Relevance
“…Polyamidoamine dendrimers (PAMAM-G3) are soluble, cationic nucleic acid-binding polymers (NABPs) that prevent TLR activation and inhibit in ammation, and have demonstrated therapeutic e cacy in preclinical studies of acute liver failure, 17 lupus, 18 cancer metastasis, 19 in uenza infection, 20 and sepsis. 21 We have shown that insoluble cationic nucleic acid-binding nanoparticles (NABNs) exhibit greater therapeutic e cacy than soluble NABPs and lower toxicity in murine sepsis and rheumatoid arthritis models. [21][22][23] Here we develop NABNs speci cally for periodontitis by coating bone-mimicking selenium-doped hydroxyapatite nanoparticles (SeHANs) with PAMAM-G3, and compare the therapeutic activity of these NABNs with that of soluble PAMAM-G3 polymers in vitro and in a ligature-induced periodontitis murine model.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…Polyamidoamine dendrimers (PAMAM-G3) are soluble, cationic nucleic acid-binding polymers (NABPs) that prevent TLR activation and inhibit in ammation, and have demonstrated therapeutic e cacy in preclinical studies of acute liver failure, 17 lupus, 18 cancer metastasis, 19 in uenza infection, 20 and sepsis. 21 We have shown that insoluble cationic nucleic acid-binding nanoparticles (NABNs) exhibit greater therapeutic e cacy than soluble NABPs and lower toxicity in murine sepsis and rheumatoid arthritis models. [21][22][23] Here we develop NABNs speci cally for periodontitis by coating bone-mimicking selenium-doped hydroxyapatite nanoparticles (SeHANs) with PAMAM-G3, and compare the therapeutic activity of these NABNs with that of soluble PAMAM-G3 polymers in vitro and in a ligature-induced periodontitis murine model.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…Histopathological and biochemical data of cecal ligation and puncture (CLP)-induced severe sepsis mice revealed that injected PEI-MSNPs accumulated and retained in the inflamed cecum, blocked the proinflammatory response and protected mice against multiple organ injury with negligible toxic effects in vivo. [148] The NP-based gene therapy described above, as well as the NP-enable cell therapy described earlier, [115] uncover the multitude of emerging opportunities nanomedicine can offer for the management of sepsis.…”
Section: Nanoinhibition Of Toll-like Receptors (Tlr) Signalingmentioning
confidence: 98%
“…Inspired by this principle, Dawulieti et al synthesized polyethylenimine (PEI)-functionalized mesoporous silica NPs (MSNPs, 150 nm in size) which bound to proinflammatory nucleic acids and scavenged cfDNA. [148] The scavenging activity of PEI-MSNPs resulted in the inhibition of cfDNA-triggered inflammation, the reduction of serum cytokines (TNF-, IL-6, and MCP-1) and elimination of organ damage. Histopathological and biochemical data of cecal ligation and puncture (CLP)-induced severe sepsis mice revealed that injected PEI-MSNPs accumulated and retained in the inflamed cecum, blocked the proinflammatory response and protected mice against multiple organ injury with negligible toxic effects in vivo.…”
Section: Nanoinhibition Of Toll-like Receptors (Tlr) Signalingmentioning
confidence: 99%
“…The treatment with DNase was shown to be active in several immune-mediated experimental models through the breaking of NETs and the consequent pro-inflammatory activity [ 115 , 116 ]. Another promising line of work is focused on the development of nucleic acid-binding polymers (NABPs), which can scavenge proinflammatory cfDNA to modulate inflammation at the injured site [ 117 , 118 ]. Of note, the therapeutic potential of cfDNA in this context of research should be further explored in the near future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%